Pemberdayaan Kader dan Pekerja Batik dalam Pencegahan Muskuloskeletal Disolders di Pos UKK “Kapal Sanggat” Kecamatan Pelayangan Kota Jambi - Faridah Faridah; Wanti Hasmar (Jurnal Abdimas Kesehatan (JAK), 2026)
Musculoskeletal Disorders (MSDs) are among the most common occupational health problems experienced by batik artisans due to prolonged static working postures, extended periods of bending, and repetitive movements during the batik-making process. These conditions can lead to discomfort and pain in the neck, shoulders, back, lower back, and wrists, which may adversely affect workers’ health and productivity. This program aimed to improve participants’ knowledge and skills in conducting early detection, providing education, and assisting batik artisans in preventing MSDs. The activity was conducted at the Occupational Health Efforts Post (Pos Upaya Kesehatan Kerja/Pos UKK) Kapal Sanggat through socialization sessions, health education, interactive discussions, question-and-answer activities, and demonstrations of ergonomic stretching exercises. Evaluation was carried out using pre-test and post-test questionnaires to assess changes in participants’ knowledge levels. A total of 20 participants were involved, consisting of 6 Pos UKK cadres and 14 batik artisans. The results showed a substantial improvement in knowledge, with the proportion of participants in the good knowledge category increasing from 33.3% to 83.3%, while the poor knowledge category decreased to zero following the intervention. Furthermore, all participants were able to correctly perform the ergonomic stretching exercises. This program was effective in enhancing the capacity of both Pos UKK cadres and batik artisans and strengthening the role of Pos UKK in the sustainable community-based prevention of MSDs.